2006
DOI: 10.1111/j.1467-789x.2006.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevention of overweight and obesity in children and adolescents: a review of interventions and programmes

Abstract: Summary Overweight and obesity are serious, large‐scale, global, public health concerns requiring population‐based childhood overweight and obesity prevention. The overall objective of this review is to identify aspects of successful childhood overweight prevention programmes. This objective will be met by assessing existing interventions quantitatively as well as qualitatively, identifying efficacy, effectiveness and implementation, and evaluating potential adverse effects of previous studies. This review was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
501
3
33

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 543 publications
(550 citation statements)
references
References 73 publications
13
501
3
33
Order By: Relevance
“…Another review found that 17 of 25 studies resulted in statistically significant reduction in BMI. 20 On the other hand, results from interventions aimed at obesity prevention have not been as promising. A recent meta-analytic review of 64 obesity prevention programs (46 trials) for children and adolescents showed that 79% of programs did not produce statistically reliable weight-gain-prevention effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another review found that 17 of 25 studies resulted in statistically significant reduction in BMI. 20 On the other hand, results from interventions aimed at obesity prevention have not been as promising. A recent meta-analytic review of 64 obesity prevention programs (46 trials) for children and adolescents showed that 79% of programs did not produce statistically reliable weight-gain-prevention effects.…”
Section: Discussionmentioning
confidence: 99%
“…19 Several systematic reviews of childhood obesity programs have been published. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] With the exception of one recent review 20 and an earlier review conducted by our team in collaboration with the Community Guide Branch of the Center for Disease Control and Prevention (CDC), 25 this work is unique in that it focuses specifically on studies undertaken in schools. Previous reviews have focused solely on the prevention of obesity 22 or weight loss interventions among already overweight children.…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors have systematically reviewed the evidence of interventions aimed at preventing child obesity [28][29][30] . The conclusions of these reviews have been consistent, in part due to the limited number of highquality, medium-long term, randomised controlled trials.…”
Section: Prevention Of Overweightmentioning
confidence: 99%
“…The conclusions of these reviews have been consistent, in part due to the limited number of highquality, medium-long term, randomised controlled trials. A recent review by Doak et al 30 gave rise to some controversies. More of the non-effective studies in this review intervened both on diet and physical activity, included physical activity outside school as part of the intervention and targeted the physical environment as a strategy to increase access to healthy lifestyles for the intervention group.…”
Section: Prevention Of Overweightmentioning
confidence: 99%
“…Finally, given the paucity of studies where the intervention and/or follow-up phases lasted for a minimum of 1 year, shorter term studies have also been included in many reviews, e.g. Summerbell et al 24 and Doak et al 30 In contrast to the earlier reviews in which methodological rigour was the main yardstick by which intervention studies were appraised, more recent reviews have intentionally been more inclusive and diverse in their appraisal process in order to identify elements of best practice for the prevention of obesity at the population level 24,30,31 . Without doubt, the most comprehensive and inclusive synthesis of the literature to date has been the one carried out by Flynn et al 31 in which 500 reports were evaluated not only for their methodological rigour, but also for programme development/evaluation and the degree to which they encompassed the principles of population health and immigrant health.…”
Section: Introductionmentioning
confidence: 99%